ANALISIS PRODUKSI DAN PENDAPATAN USAHATANI PADI SAWAH DI DESA MASANI KECAMATAN POSO PESISIR KABUPATEN POSO - Morante, Oktian; Christoporus, Christoporus; Tondi, Karlina Muhsin (AGROTEKBIS : JURNAL ILMU PERTANIAN (e-journal), 2023)
The objectives of this research were to determine the effects of inputs including land area, seeds, urea fertilizer, phonska fertilizer, and labor on rice production, and to determine the income generated from lowland rice farming in Masani Village, Poso Pesisir Sub District, Poso District. Respondents of 58 household head were selected using a census method. Data analysis was performed using the Coob-Douglas function analysis and income analysis. The findings of the research revealed that 89.50% of the variation in the rice production can be attributed to the effects of the land area, seeds, urea fertilizer, phonska fertilizer, and labor. The remaining 10.50% of the variation was influenced by other factors that were not accounted for in the estimation model. On average, the farmers in Masani Village, earn approximately IDR 15,233,951.35/ha/planting season.